COVID-19 at War: The Joint Forces Operation in Ukraine. (25th October 2022) - Quinn V, John M.; Dhabalia, Trisha Jigar; Roslycky, Lada L.; Wilson V, James M.; Hansen, Jan-Cedric; Hulchiy, Olesya; Golubovskaya, Olga; Buriachyk, Mykola; Vadim, Kondratiuk; Zauralskyy, Rostyslav; Vyrva, Oleg; Stepanskyi, Dmytro; et al.
Abstract: The ongoing pandemic disaster of coronavirus erupted with the first confirmed cases in Wuhan, China, in December 2019, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) novel coronavirus, the disease referred to as coronavirus disease 2019, or COVID-19. The World Health Organization (WHO) confirmed the outbreak and determined it a global pandemic. The current pandemic has infected nearly 300 million people and killed over 3 million. The current COVID-19 pandemic is smashing every public health barrier, guardrail, and safety measure in underdeveloped and the most developed countries alike, with peaks and troughs across time. Greatly impacted are those regions experiencing conflict and war. Morbidity and mortality increase logarithmically for those communities at risk and that lack the ability to promote basic preventative measures. States around the globe struggle to unify responses, make gains on preparedness levels, identify and symptomatically treat positive cases, and labs across the globe frantically rollout various vaccines and effective surveillance and therapeutic mechanisms. The incidence and prevalence of COVID-19 may continue to increase globally as no unified disaster response is manifested and disinformation spreads. During this failure in response, virus variants are erupting at a dizzying pace. Ungoverned spaces where nonstate actors predominate and active war zones may become the next epicenter for COVID-19 fatality rates. As the incidence rates continue to rise, hospitals in North America and Europe exceed surge capacity, and immunity post infection struggles to be adequately described. The global threat in previously high-quality, robust infrastructure health-care systems in the most developed economies are failing the challenge posed by COVID-19; how will less-developed economies and those health-care infrastructures that are destroyed by war and conflict fare until adequate vaccine penetrance in these communities or adequate treatment are established? Ukraine and other states in the Black Sea Region are under threat and are exposed to armed Russian aggression against territorial sovereignty daily. Ukraine, where Russia has been waging war since 2014, faces this specific dual threat: disaster response to violence and a deadly infectious disease. To best serve biosurveillance, aid in pandemic disaster response, and bolster health security in Europe, across the North Atlantic Treaty Alliance (NATO) and Black Sea regions, increased NATO integration, across Ukraine's disaster response structures within the Ministries of Health, Defense, and Interior must be reinforced and expanded to mitigate the COVID-19 disaster.